Efeito do exercício físico (natação) sobre a glicemia e triglicéridos de ratas prenhas diabéticas e repercussão sobre os fetos - Lopes, Gabriela Andrade Piemonte [UNIFESP] (2009)
This research aims to study the materno-fetal repercussion of the swimming on the glucose, triglycerides levels, weight gain and maternal food intake, and also the number and weight of offspring at birth. We used 24 Wistar adult female rats, with 235 g of initial weight, distributed into 4 groups: sedentary pregnant control (CGS) (n=6), trained pregnant control (CGT) (n=6), sedentary pregnant experimental (EGS ) (n=6) and trained pregnant experimental (EGT) (n=6). It was used streptozotocin-induceddiabetes in the experimental group, and the rats were paired for copulation, and the confirmation by the presence of sperm in the smear. The control of glucose and triglycerides levels were made in the four groups, starting from day zero of gestation (collection 1), followed by the 7th (collection 2), 14th (collection 3) and 19th days (collecting 4). The physical training (swimming) was performed five times a week (60 minutes), for three consecutive weeks until the day of spontaneous delivery. The maternal weight and food intake were daily controled, and after birth, the offsprings were counted and weighed. Therefore, physical exercise (swimming) of moderate intensity was able to significantly reduce the glycemic values, especially in pregnant diabetic rats, also, benefits in the profile of triglycerides, and not to promote change on the fetus.